Digitalisasi Wakaf Tunai: Peluang dan Tantangan Pengelolaan Aset Umat di Era 5.0 - Muhammad Sauqi; Novia Novia; Siti Nabila (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2026)
This study aims to evaluate the effectiveness of digital transformation in the 5.0 era in transforming latent cash waqf assets into productive capital capable of sustainably driving the community’s economy. The study employed a qualitative approach using a literature review method. Data were obtained through literature searches and official documents from the Indonesian Waqf Board, then analyzed descriptively to obtain comprehensive conclusions regarding the effectiveness of digital systems in cash waqf management. The results indicate that financial technology (fintech) such as QRIS, crowdfunding, Islamic banking applications, and digital wallets (e-wallets) are capable of overcoming conventional bureaucratic barriers through the concept of “micro waqf,” which is accessible to all levels of society. Based on the Technology Acceptance Model (TAM) theory, ease of digital access has been proven to increase public interest in waqf because it reduces administrative barriers and concerns regarding transaction amounts. In addition, real-time data-based reporting systems also improve transparency and accountability in waqf management. Therefore, the digitalization of cash waqf in the 5.0 era serves as a form of social engineering in collecting collective funds to sustainably support sharia-based productive sectors.